PENGEMBANGAN MEDIA BIG BOOK BERGAMBAR BERMUATAN KEARIFAN LOKAL KEDIRI PADA MATERI MENGENAL KOSAKATA KELAS 1 SD - Oktaviana, Cindy; Rian Damariswara; Farida Nulaila Zunaidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the results of observations, that 50% of students have grades below the KKM. This is because understanding in receiving the material is still lacking resulting in low vocabulary mastery. This is due to the lack of use of teaching media during the learning process. This research aims to develop big book teaching media with pictures containing local Kediri craftsmanship in class I vocabulary material. The research method used is development (R&D) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, evaluation. The product trial subjects were carried out on 23 class I students. The instruments used were the students' learning results. From the results of the trials carried out, it was found that the effectiveness of the big book teaching media containing Kediri local wisdom in vocabulary material was obtained with an average score of 90 in the very effective category. From the results of this research, it can be concluded that the development of illustrated big book media containing Kediri local wisdom is suitable for use in learning.